On the Historicity of Scientific Objects - Arabatzis, T. (Erkenntnis, 2011)
The historical variation of scientific knowledge has lent itself to the development of historical epistemology, which attempts to historicize the origin and establishment of knowledge claims. The questions I address in this paper revolve around the historicity of the objects of those claims: How and why do new scientific objects appear? What exactly comes into being in such cases? Do scientific objects evolve over time and in what ways? I put forward and defend two theses: First, the ontology of science is so rich and variegated that there are no universally valid answers to these questions. Second, we need a pluralist account of scientific objects, a pluralist metaphysics that can do justice to their rich diversity and their various modes of being and becoming. I then focus on hidden objects, which are supposed to be part of the permanent furniture of the universe, and I discuss their birth and historicity: They emerge when various phenomena coalesce as manifestations of a single hidden cause and their representations change over time. Finally, I examine the conditions under which an evolving representation may still refer to the same object and I illustrate my argument drawing upon the early history of electrons.